Pengaruh Pembelajaran Akidah Akhlak Terhadap Perilaku Sosial Siswa Kelas VII di MTs Negeri 2 Bangka - Ramadhani, Endes; Rahman, Priyanggo Karunia (LENTERNAL: Learning and Teaching Journal, 2023)
The primary purpose of ethical learning is to educate students to be good and respected individuals. Students must be diligent, honest, disciplined, tolerant, and responsible, maintain social and personal harmony, and create a safe and peaceful environment. The aim of this study is to find out whether Akidah Akhlak learning affects the social behavior of students in MTS State 2 Bangka and how much the impact of such learning is on the social behavior of students. This research uses quantitative and correlational methods. This study involved 105 students. The results of a sample of 51 students were obtained through a simple random sampling method with a Slovin formula. Research using a lift, or question, and regression analysis is done with simple linear regression. The results of the study showed that students at the State MTS 2 Bangka have a significant relationship with their social behavior. The simple regression test results, obtained from a thitung value of 6.570 and a Sig value of 0.000, show this. At free degrees df = 50-2 = 48, the ttable value is obtained at 1,677. Therefore, it can be concluded that thitung is larger than ttable (6,570 is larger than 1,677), and the Sig value is less than 0.05 (0,000 kurang dari 0,05). The results showed that academic learning (X) affects the social behavior (Y) of students in grade VII at MTS State 2 Bangka. Thus, Ha is accepted, and HO is automatically rejected. Furthermore, with the R square value of 47.3%, we can find that the influence of the free variable on the bound variable is 47.3%, with other components not considered as variables affecting 52.7%.